Conversational Implicature in Kim Namjoon’s UN Speech: A Paul Grice Pragmatic Implicature Analysis - Aditya, Haiba Pradita (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study aims to analyze the conversational implicature in the speech of Kim Namjoon (RM), leader of South Korean music group BTS, at the 2018 United Nations General Assembly. The analysis was conducted using a pragmatic approach based on Paul Grice’s theory of conversational implicature, as explained in the book Doing Pragmatics by Peter Grundy. The method used is descriptive qualitative with content analysis technique, which aims to reveal the implied meanings of the utterances in the speech. The results showed that RM strategically utilized violations of Grice’s maxims (Quantity, Quality, Relevance, and Manner) to produce strong conversational implicature. The violations do not reduce the effectiveness of the message, but rather strengthen the persuasive, emotional, and universal power of the speech. The implicature reflects values such as courageous self-acceptance, empathy, and the urge to express one;s true self. The findings confirm that the communication strategies used by RM in his speech are an example of effective application of pragmatics in the context of cross-cultural and global communication.